Rewriting Mazeppa: Meaning and communication in Liszt's virtuoso and program music. (December 2018) - Rodriguez, Hugo
Musical virtuosity is often studied with an emphasis on the outstanding skills of the performer and their sensory and emotional effects on the listener. However, Franz Liszt, one of the main virtuosos in music history, was convinced that what matters in virtuosity is its specific function within the semantic and communicative processing of music. This article proposes a theoretical framework to further investigate Liszt's intuitions in light of contemporary research on musical meaning and communication. First, we analyze philological data concerning Liszt's creative process in the Mazeppa works, a set of works including both his virtuoso and program music. Second, we compare our results with recent research on music semantics based on inferential processes about the composer/performer's intentions (Antović, Stamenković, & Figar, 2016; Schlenker, 2017). We criticize the associationist hypothesis (the idea that the composer's intention is that the listener infers an association between the music and a real or fictional state of the world) and we defend a causalist hypothesis (the idea that the composer's intention is that the listener recognizes the music as being an intentional "rewriting" of the states of the world, mental or physical, that are the causes of the music itself). Third, we suggest that what distinguishes Liszt's virtuoso and program music rewritings are the visual and gestural components of two listening experiences: the virtuoso music "rewrites" its episodic causes (memories, personal experiences) whereas the program music "rewrites" its genetic causes (the work's creative path and intertextual relations).